Influence of ZnSe:Te substrate's surface morphology on their optical properties - В. П. Махний; И. И. Герман; Г. И. Бодюл; И. М. Сенко (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The authors have experimentally established, that etching of ZnSe:Te substrates in CrO3:HCl=2:1 and H2SO4:H2O2=3:1 solutions leads to formation of mirror and matte surfaces. Analysis of the topogram obtained by an atomic power microscope showed that the matte surface is a set of equally oriented pyramids with basis size 2–5 μm and each of them is an association of nanopyramids with 10-100 nm lateral size. In such samples, the wide photoluminescence band at 2.7–3.8 eV is a result of dimensional quantization in smaller nanocrystals. The latter also causes an observed decrease of transmission coefficient of substrates with matte surface in comparison to those with mirror surface owing to increase of light scattering processes.